Anne of the Green Gables - Montgomery, Lucy Maud (Great Britain : Wordsworth Classics, 1994)
Fiction.
Keywords: Canada-History-1867-1914 -- Fiction; Country life-Prince Edward Island -- Fiction; Friendship -- Fiction; Prince Edward Island-History-20th century -- Fiction